Not all emotions are equal:Fear chemosignals lower awareness thresholds only for fearful faces - Semin, Gün R. (2020)
Exposure to body odors (chemosignals) collected under different emotional states (i.e., emotional chemosignals) can modulate our visual system, biasing visual perception. Recent research has suggested that exposure to fear body odors, results in a generalized faster access to visual awareness of different emotional facial expressions (i.e., fear, happy, and neutral). In the present study, we aimed at replicating and extending these findings by exploring if these effects are limited to fear odor, by introducing a second negative body odor - i.e., disgust. We compared the time that three different emotional facial expressions (i.e., fear, disgust, and neutral) took to reach visual awareness, during a breaking continuous flash suppression paradigm, across three body odor conditions (i.e., fear, disgust and neutral). We found that fear body odors do not trigger an overall faster access to visual awareness, but instead sped-up access to awareness specifically for facial expressions of fear. Disgust odor, on the other hand, had no effects on awareness thresholds of facial expressions. These findings contrast with prior results, suggesting that the potential of fear body odors to induce visual processing adjustments is specific to fear cues. Furthermore, our results support a unique ability of fear body odors in inducing such visual processing changes, compared to other negative emotional chemosignals (i.e., disgust). These conclusions raise interesting questions as to how fear odor might interact with the visual processing stream, whilst simultaneously giving rise to future avenues of research.